THE USE OF QUESTIONING STRATEGY IN EFL CLASSROOM (RETAIN, 2020)
The goals of learning English as foreign language are to make the student able to understand English and use it communicatively. It can be achieved if the use of English is habituated in the classroom. One of activity in interactive classroom to make students able to use English communicatively is by implementing questioning strategy. This study focus on the implementation of questioning strategy in EFL classroom and the types of questioning strategy based Blosser’s schema. This study was qualitative research which used case study design. The subjects were one of English teacher and 34 tenth grader’s students in one of senior high school in Ponorogo. The instrument used by the researcher were field note, video recorder, interview guidelines, and audio recorder. From the result of observation and interview, the teacher implemented questioning strategy in whole of lesson. In implementing the strategy, the teacher had purposes, including increasing the students’ critical thinking, ability, and activeness; adjusting the material based on the students’ need; motivating the students to be active participate; provoking the students to recall the previous material and to discuss the material together; judging the students’ ability; and helping the teacher to assess the effectivenenss of the material. Another result showed that in implementing the strategy, the teacher used five guidelines, including ask the question, pause, call the learner’s by name or let the students answer by their inisiative, listen the answer, and emphasize the correct answer. The teacher mostly used three types of questioning strategy, including probing question, factual question, and divergent question. In each questioning strategy, the teacher used five types of question, which included clarifying, prompting, redirectering, simple bit of information, and divergent.